Pengaruh Variasi Produk, Harga Dan Store Atmosphere Terhadap Loyalitas Pelanggan Warung Chato-Chato Tangerang - Agustine Yulandari; Andy (Fakultas Bisnis, 2025)
This study aims to examine the influence of product variation, price, and store atmosphere on customer loyalty of Tangerang chato-chato stalls. The research method used is quantitative. This research was conducted by distributing questionnaires to 119 respondents. The data obtained in this study was processed using SPSS version 22 software. From the results of the validity and reliability test, the value of the test results of the question indicator of each variable (r calculation) > 0.1809 (r table). From the results of the multiple linear analysis, the equation Y = 1.010 + 0.292(X1) + 0.415 (X2) + 0.264(X3) + e from the results of the determination coefficient was obtained from model 1 which was 39.9%, model 2 which was 53.9% and model 3 which was 56% regarding the influence of product variation, price and store atmosphere on customer loyalty. Based on the t-test of model 1, t calculates product variation, which is 3,007 > 1.98063 (t table) with a significant value of 0.003 < 0.05, t calculates model 2 at a price of 4,173 > 1.98063 with a significance value of 0.000 < 0.05 and t calculates model 3 store atmosphere, which is 2,616 > 1.98063 with a significance level of 0.010 < 0.05 based on the three models, it can be concluded that Ho is rejected and Ha is accepted for these variables. From the results of the F test, 48,838 > 2.68 f table with a significance value of 0.000 < 0.05, then Ho was rejected and Ha was accepted.